Diagnosis, treatment and management of apathy in Parkinson’s disease: a scoping review - Zahinoor Ismail; Jayna Holroyd-Leduc; Tamara Pringsheim; Zahra Goodarzi; Bria Mele; Shinia Van (BMJ Open)
Objective To conduct a scoping review of the literature on apathy in Parkinson’s disease (PD), to better understand how apathy in Parkinson’s disease is diagnosed, treated and managed.Methods MEDLINE, Embase, PsycINFO, CINAHL, Cochrane Central Register of Control Trials and Cochrane Database of Systematic Reviews were searched to 17 May 2017. An updated review was run from 17 May 2017 to 28 January 2019. The grey literature was searched using the CADTH Grey Matters tool. Original peer-reviewed research was included if it included individuals with PD and apathy. Non-original data was only included if it was in the form of meta-analysis. All information regarding diagnosis, treatment and management of PD was extracted. Citation screening and extraction were performed in duplicate.Results From 11 375 citations, 362 articles were included in the final review. The majority of included studies focussed on prevalence, with few studies examining treatment. Twenty screening tools for apathy were identified. Fifty per cent of treatment studies were randomised control trials (RCTs). RCTs applied treatment methods including: exercise, mindfulness, rotigotine (Neupro) transdermal patch and rivastigmine (Exelon).Conclusions This review identified a large body of literature describing current knowledge on diagnosing, treating and managing apathy in PD. Future research should aim to detect an ideal screening tool for apathy in PD, to identify the best treatment options for apathy and the variety of comorbidities it may present with and finally aim to better understand postoperative apathy in those with deep brain stimulation.